The Behaviour Of The Current Account Balances Of ASEAN-5 Members - Ismail, Hamizun (2007)
Current account conveys information about the actions and expectations of all market participants in an open economy; it reflects the stance of macroeconomic policies and provides information about the behaviour of economic agents. Therefore, the needs for greater understanding about the behaviour of the current account are becoming increasingly vital, as institutional structures dealing with macroeconomic policies cannot simply be copied from one country to another. This dissertation empirically examined the movement of the current account balances for the ASEAN-5 countries, namely Indonesia, Malaysia, Philippines, Singapore and Thailand, under four main issues: the intertemporal optimization approach to the current account, the twin-deficits hypothesis, the relationship between current account and investment, and the temporary and permanent shocks of the current account balance and the real exchange rate. Several important results emerged from this study. First, the present value model effectively captures the magnitudes and directions of the current account balances for four out of five ASEAN-5 countries over the period of the study, thus favored the proposition that the countries’ expectations about future movement in net output are reflected by today’s current account. Second, the data supported the twin deficit hypothesis for the ASEAN-5 countries except Indonesia, and that the budget deficit plays a weakly exogenous role with respect to the current account deficit. This is an important finding because it implies that fiscal policy is effective in influencing current account balance. Third, our finding indicated that the ASEAN-5 have relied on domestic savings to finance their investment, thus agreeing with the proposition that developing countries only participate partially in the world’s capital market, as a result of the lack of sophisticated domestic capital market in the developing countries. Forth, our finding suggested that the temporary shock depreciates the currency so much that the current account improves over the short term, while over the longer term, the current account effect fades away as the exchange rates stabilize.